Observational Study of Sociodemographic Profile on Female Autopsy Cases of J.L.N Medical College, Ajmer - Nirjhar Mathur1 , Sumer Singh2 , R K Mathur3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction:- Unnatural deaths of females in a particular geographic area is the reflection of its law andorder situation. Lower incidences indicate presence of peace, harmony and security in the society. Presentstudy is designed to determined unnatural deaths of females in Ajmer city. This study includes the varioussocio-etiological aspects of un-natural female death. The findings of our study is useful in planning ofprevention polices.Aims & objectives:- -To collect the statistical data of Autopsy cases of unnatural female death cases broughtto J.L.N. Hospital, Ajmer mortuaryObjectives:- To study the various socio demographic data of autopsy cases of un-natural deaths of females.Material and Method:- Population Universe:-All Medico-legal Autopsies conducted in Department of Forensic Medicine and Toxicology at J.L.N. MedicalCollege and Associated Group of Hospitals, Ajmer. These were total 953 medico-legal autopsies in numberCase Study:- As present study comprised 170 autopsy cases of unnatural female deathsStudy period:- 1st April 2019 to 31st March 2020Method:- Performa for study was prepared on the basis of information obtained from Autopsy, Panchnama,questionnaire of relatives and all collected data were put into the master-chart, which was prepared and thenfeed into the computer in Excel worksheet and then analyzed.Observation & Results:- More than half of victims were married (69.41%) Among the married women,maximum cases (61.86%) were of more than 7 years of marriage life. Highest number of cases (40%)was seen in Summer. Literate women comprise of about 66.47% of total cases. Highest number of cases(50.58%) was of accidental in nature. Suicidal deaths constituted more than half of deaths which occurredwithin in seven year of married life. Burns (30.58%) was most common cause of death. It was also same inroad traffic accidental deaths (30.58%). Most common poison which causes 66.66% deaths is OPC whileSecond most common was ALP (13.88%).Recommendations:-our target group for prevention of unnatural deaths should be married woman of first twoyear of married life of age segment of middle economic literate Hindu group